2013
DOI: 10.1542/peds.2012-1622
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Amblyopia: What Have We Learned From PEDIG Trials?

Abstract: Amblyopia is the most common cause of preventable visual loss in children. This article reviews treatment options, durations, and efficacy in randomized multicentered trials conducted by the Pediatric Eye Disease and Investigator Group in the last decade. Parents and patients should be counseled that many forms of treatment are efficacious, allowing the option of choice of best-tolerated treatment method. Compliance is key to successful treatment. The course of treatment is likely at least 6-12 months, with ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 37 publications
1
58
0
5
Order By: Relevance
“…1 It is the most common cause of preventable visual impairment in children with an incidence rate of up to 3.5%. 2 The amblyopic syndrome impacts amblyopes to different extents depending on differing factors, such as the status of binocular functions and the type of amblyopia. Strabismus (an eye turn), anisometropia (differences in refractive errors), or other causative factors, which occlude the visual axis (form deprivation), 1 can challenge the visual system with differing patterns of visual acuity (VA) and contrast sensitivity losses.…”
mentioning
confidence: 99%
“…1 It is the most common cause of preventable visual impairment in children with an incidence rate of up to 3.5%. 2 The amblyopic syndrome impacts amblyopes to different extents depending on differing factors, such as the status of binocular functions and the type of amblyopia. Strabismus (an eye turn), anisometropia (differences in refractive errors), or other causative factors, which occlude the visual axis (form deprivation), 1 can challenge the visual system with differing patterns of visual acuity (VA) and contrast sensitivity losses.…”
mentioning
confidence: 99%
“…Researchers demonstrated that weekendonly atropine use was as effective as daily use and 2 hours of patching improved moderate to severe amblyopia in children [17]. The PEDIG studies confirmed that the initial choice of treatment was not binding; if a patient did not respond satisfactorily, it was reasonable to prescribe more intense or different treatment [13,18]. Reduced lengths of regimen are also effective, with the potential maximum vision in an amblyopic eye being reached in 3 to 4 months with treatment compliance.…”
Section: Resultsmentioning
confidence: 99%
“…A series of recent randomized controlled treatment trials from the PEDIG have provided a more evidence-based approach to treatment, offering novel evidence that lesser amounts of patching are as effective as more intense regimens and that atropine penalization is often as effective as patching [13][14][15][16]. Researchers demonstrated that weekendonly atropine use was as effective as daily use and 2 hours of patching improved moderate to severe amblyopia in children [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O tratamento da ambliopia é possível se o obstáculo ao desenvolvimento visual normal for removido precocemente. Por isso, justifica-se a importância da detecção precoce e do início do tratamento logo nos primeiros anos de vida 35,36 . Segundo a Academia Americana de Oftalmologia, o melhor momento para tratamento da ambliopia corresponde aos anos da pré-escola A prevalência da cegueira infantil varia de acordo com a situação socioeconômica de cada região 40 .…”
Section: Anormalidades Oculares Em Criançasunclassified